PSYCHOLOGICAL PROBLEMS THAT ARE ENCOUNTERED BY ENGLISH FOREIGN LANGUAGE LEARNERS - Astuti, Nanda; Fitriani, Siti Sarah; Kismullah, Kismullah (Premise: Journal of English Education and Applied Linguistics, 2023)
This study aims to investigate the psychological problems perceived by students in speaking English and to examine factors leading to the problems as well as the students' efforts to cope with the problems. A mixed-method design was used in conducting this study. Data collection was done by distributing a questionnaire to sixty-four participants and interviews conducted with ten students participants of MAS Ulumul Quran in Aceh. The data were analyzed using quantitative data analysis (frequency and percentage formula), and interactive models of qualitative data analysis (data condensation, data display, and conclusion drawings). The findings revealed that the most common psychological problems faced by the students were fear of making mistakes with followed by speaking anxiety, lack of confidence, shyness, and lack of motivation. Those problems were caused by their inability to speak English, an unsupportive learning atmosphere, less speaking practice, negative attitude towards English,  afraid of being mocked and underestimated by friends, afraid of being misunderstood, and terrified of appearing foolish. To cope with the problems, the students did many efforts such as pretending not to be panicked, making jokes,  asking friends’ help, preparing before speaking, avoiding eye contact, inviting friends to practice English, motivating themselves to speak English by reading a motivational book or watching motivational videos, etc. In this regard, it was suggested that the teacher should encourage students to stop thinking that English is difficult to learn, stop worrying about friends’ judgments, and stop thinking about mistakes they possibly made when speaking English in the classrooms. Besides, the teacher should encourage students to practice English with peers or their classmates. Finally, the researcher recommends for further researcher to investigate the teacher’s perception of students’ psychological problems and how they overcome the problems when teaching English.